Growth versus environment in dynamic models of capital accumulation. Issue 2 (2002) - Asada, Toichiro
Abstract : In this paper, we study the economic implications of the trade off between growth and environment in the context of dynamic models of capital accumulation. The collective solution is formulated in terms of dynamic optimization of the central planner, and the decentralized solution is formulated in terms of differential game between workers and capitalists. We compare the economic properties of two solutions.